The Landscape of DNA Methylation Associated With the Transcriptomic Network of Intramuscular Adipocytes Generates Insight Into Intramuscular Fat Deposition in Chicken - Zhang, Meng; Li, Donghua; Zhai, Yanhui; Wang, Zhengzhu; Ma, Xiangfei; Zhang, Daoyu; Li, Guoxi; Han, Ruili; Jiang, Ruirui; Li, Zhuanjian; Kang, Xiangtao; Sun, Guirong (Frontiers in Cell and Developmental Biology, 2020)
As one of the most important factors influencing meat quality, intramuscular fat (IMF) is regulated by genetics, nutrition and environment. However, the epigenetic molecular mechanism underlying poultry IMF deposition remains poorly understood. In the present study, we focused on the DNA methylation, which usually regulate genes expression in the post-transcription level. To investigate the crucial role of DNA methylation on the IMF deposition, chicken intramuscular preadipocytes were isolated and cultured in vitro, and a model of intramuscular adipocyte differentiation was constructed. Combined the whole genome bisulfite sequencing (WGBS) and RNA-Seq technologies, we identified several methylated genes, which mainly affecting fatty acid metabolism and muscle development. Furthermore, we reported that DNA methylation regulate intramuscular adipogenesis by regulating the adipogenetic genes, such as collagen, type VI, alpha 1 (COL6A1) thus affecting IMF deoposition. Overexpression of COL6A1 increasing the lipid droplet and inhibits cell proliferation by regulating CHAD and CAMK2 in intramuscular adipocytes, while knockdown of COL6A1 having the opposite effect. These findings contribute to a better understanding of epigenetic regulation mechanism in the adipogenesis and poultry IMF deposition.